Фактор адресованості в оцінному дискурсі - Крисанова, Тетяна Анатоліївна; Krysanova, T. A. (Волинський академічний дім, 2007)
Стаття присвячена дослідженню фактора адресованості в оцінному дискурсі. Висвітлюється роль адресата в продукуванні оцінного дискурсу. Виділяються модифікації типів адресата в оцінному дискурсі. The article focuses on the study of evaluative discourse in relation to the addressee. The role of the addressee in the production of the evaluative discourse is highlighted. The main linguistic modifications of the addressee are determined and analyzed.
Addressee factor in the evaluative discourse
Keywords: адресат, оцінка, дискурс, модифікація; addressee, evaluation, discourse, modification